Arte-experimento: o bailado narrativo de Cara-de-Bronze - Corá, Larissa Thomaz [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
“Cara-de-Bronze” é uma das narrativas mais experimentais de João Guimarães Rosa por apresentar uma arquitetura textual construída sobre variadas camadas discursivas que movimentam substratos culturais implícitos e explícitos, relacionados tanto à cultura ocidental, como, por exemplo, o medievalismo e a tradição literária da novela de cavalaria, quanto à cultura oriental, como os upanixades indianos citados em forma de nota de rodapé. Seu caráter multifacetado é tal que ainda é passível de problematização a inscrição dessa narrativa em um gênero (ou forma narrativa) definido, pois nela há rastros dos três grandes gêneros – o Lírico, o Épico (narrativo) e o Dramático – e, ainda, dentro de cada um , outras pistas que levam à percepção de variadas formas, tanto do poema, da cantiga e do cantar de gesta, quanto da epopéia, do conto e da novela; e mais ainda, do teatro e do cinema. Essa implosão de fronteiras discursivas revela a dualidade essencial da obra, sua fundação alicerçada em dois suportes: um arcaico e outro moderno, percebidos na tradição literária e na experimentação formal. O intuito, portanto, é verificar o modo como a sobreposição de planos culturais e de enredo, assim como a transposição de gêneros e de códigos artísticos mobilizam metalinguisticamente tais...

“Cara-de-Bronze” is one of João Guimarães Rosa’s most experimental narratives, for it presents a textual architecture built over several discursive layers that move implied and explicit cultural substrates related both to Western culture, as for example the medievalism and the literary tradition of medieval novels, and to Eastern-Asian culture, as the Indian Upanishads quoted as footnote. Its multi-facial characteristic is so intense that inserting this narrative into a defined genre (or narrative form) comes to a problem, because there are traces of the three great genres – Lyric, Epic, and Tragedy – in it, and, yet, inside each of them, other clues that reveal the perception of several forms, both from poetry, from folk songs or chanson de geste, and from the epopee, from the short-stories and from the novella; and, furthermore, from theater and cinema. This implosion of discursive boundaries shows the work of art’s dual essence, its foundation built upon two bases: one archaic and the other modern, noticeable in the literary tradition and in the formal experimentation. The aim is, therefore, to verify how the overlaying of cultural plans and of plot, as well as the transposition of genre and artistic codes, mobilize metalinguistically the inter- and intra-discursive layers and make Rosa’s work an aesthetical experiment whose objective is pointing out the artistic process itself and the poetical effect that follow as a result. With the general aim of investigating this narrative, the analysis here developed see as relevant the theories which are based on the critical current that regards the text as an object. From the concepts of formal experimentation, discussed by Antonio Manoel dos Santos Silva (2009), a path follows based on literary French semiotics, greimasian, rethought by Denis Bertrand (2003), on cultural semiotics, from Tartu’s school, edified... (Complete abstract click electronic access below)
Keywords: Rosa, João Guimarães, 1908-1967 - Cara de bronze - Crítica e interpretação; Literatura brasileira - História e crítica; Contos brasileiros - História e crítica; Formal experimentation; Metalinguistics; Narrative; Art